Emerging trends in labour legislation and policy in the SADC region : the experiences of Botswana and Swaziland in the context of the ILO convention on freedom of association and protection of the right to organise (C.87) - Ntumy, Emmanuel K B (Not Specified, 2023)
The advent of the Southern African Development Community (SADC) brought with it a · euphoric expectation of instantaneous transformation of the sub-region into a vibrant, viable economic haven for its inhabitants. Time and reality have since reduced this euphoria to disillusionment. This state of affairs has resulted in a lot of introspection leading to vital questions about the readiness and capacity of the member states to let go of their national sovereignty as a price for more meaningful regional integration. Embedded in this is the major question of how the labour law regimes have lent themselves to change and whether they can be transformed into engines of growth that can facilitate employment within internationally acceptable environments. To attempt to answer this question, one needs to examine closely the individual domestic situations in order to determine how strong differences are in the context of international labour standards such as the very basic freedom of association and protection of the right to organise. The examination of • Botswana and Swaziland was therefore undertaken for this purpose. It has led us to the conclusion that essentially, labour legislation in these countries is common in many significant respects, unwilling to approximate to expected international standards but flexible enough for potential harmonization and transformation. This dissertation is however fairly inconclusive given the size of the SADC itself. It is therefore only a pointer, a part of the critical foundation of enquiry. It is thus only part of the preliminary survey for the roadmap that needs to be drawn on which a workable integration in the SADC could be built in the future.